Life is a startup what founders can teach us about making choices and managing change - Wasserman, Noam. (Stanford Stanford Business Books, 2019)
This book shows us how to apply the habits of the most successful startup founders to our everyday lives. Like entrepreneurs, we all deal with uncertainty, toughdecision making, and necessary problem solving. This book offers important advice for those envisioning a change in their lives-from contemplating the next step in a relationship to making a radical career move-and managing changes to which they've already committed. With his database of tens of thousands of entrepreneurship case studies, Noam Wasserman is able to go deeply into the entrepreneurial mindset and show us how startups provide specific lessons for crafting our most successful lives.
Includes bibliographical references and index.
Keywords: Success